Learn more about

Refine search

Results (displaying matches 1-50 of 2877) Next

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
25913.a.25913.1 25913.a \(y^2 + (x^3 + x + 1)y = x^3 - x^2 - 2x\) $\mathrm{USp}(4)$ 3
35131.a.35131.1 35131.a \(y^2 + x^3y = x^4 - 3x^3 + 4x^2 - 3x + 1\) $G_{3,3}$ 3
39017.a.39017.1 39017.a \(y^2 + (x^3 + x + 1)y = -x^5 + x\) $\mathrm{USp}(4)$ 3
39497.a.39497.1 39497.a \(y^2 + y = x^6 - x^5 + x^4 - x^3 + x^2 - x\) $\mathrm{USp}(4)$ 3
39701.a.39701.1 39701.a \(y^2 + y = x^6 - 3x^5 + 5x^3 - x^2 - 2x\) $G_{3,3}$ 3
39993.a.119979.1 39993.a \(y^2 + (x^3 + x^2 + 1)y = 2x^4 + x^3 - 2x^2 - x\) $\mathrm{USp}(4)$ 3
41411.a.41411.1 41411.a \(y^2 + (x^3 + 1)y = -3x^4 + 7x^3 - 4x^2\) $\mathrm{USp}(4)$ 3
41663.b.41663.1 41663.b \(y^2 + (x^3 + x + 1)y = x^5 - x^4 - 4x^3 + 2x\) $\mathrm{USp}(4)$ 3
42439.a.42439.1 42439.a \(y^2 + y = x^6 - 3x^5 + 3x^4 - x^3 - x^2 + x\) $G_{3,3}$ 3
44543.a.44543.1 44543.a \(y^2 + (x^3 + x + 1)y = x^4 - x^2\) $\mathrm{USp}(4)$ 3
45413.a.45413.1 45413.a \(y^2 + (x^3 + x + 1)y = -x^5 + 2x^2 - 3x\) $\mathrm{USp}(4)$ 3
46234.a.92468.1 46234.a \(y^2 + (x^3 + 1)y = -x^4 + 3x^2 - 2x\) $\mathrm{USp}(4)$ 3
49507.a.49507.1 49507.a \(y^2 + (x^3 + 1)y = 2x^4 + 3x^3 + 3x^2 + x\) $\mathrm{USp}(4)$ 3
51035.a.255175.1 51035.a \(y^2 + (x^3 + x + 1)y = -3x^4 + 5x^2 + 2x\) $\mathrm{USp}(4)$ 3
52498.a.104996.1 52498.a \(y^2 + (x^3 + x^2 + x)y = -2x^4 - x + 1\) $\mathrm{USp}(4)$ 3
53623.a.53623.1 53623.a \(y^2 + (x^2 + x + 1)y = x^6 - 2x^4 + x^3 - 2x\) $\mathrm{USp}(4)$ 3
54983.a.54983.1 54983.a \(y^2 + y = x^6 - x^5 - 3x^4 + x^3 + 3x^2 + x\) $\mathrm{USp}(4)$ 3
55112.a.110224.1 55112.a \(y^2 + (x^3 + x)y = x^4 + x^2 + 1\) $G_{3,3}$ 3
56473.a.56473.1 56473.a \(y^2 + (x^3 + x^2 + x)y = -2x^4 + x^3 - 2x + 1\) $\mathrm{USp}(4)$ 3
56629.a.56629.1 56629.a \(y^2 + (x^2 + x + 1)y = x^6 - x^2\) $\mathrm{USp}(4)$ 3
57065.a.285325.1 57065.a \(y^2 + (x^3 + x + 1)y = x^4 - 4x^3 + x^2\) $\mathrm{USp}(4)$ 3
59107.a.59107.1 59107.a \(y^2 + (x^3 + x^2 + 1)y = 2x^4 - 3x^2 - x\) $\mathrm{USp}(4)$ 3
59411.a.59411.1 59411.a \(y^2 + y = x^6 - x^5 - x^3 + 2x^2 - x\) $\mathrm{USp}(4)$ 3
59883.a.179649.1 59883.a \(y^2 + (x^3 + x + 1)y = x^5 + x^4 - 2x^3\) $\mathrm{USp}(4)$ 3
59967.a.539703.1 59967.a \(y^2 + (x^3 + x^2 + 1)y = x^4 + 2x^3 - x^2 - 2x\) $\mathrm{USp}(4)$ 3
60617.a.60617.1 60617.a \(y^2 + (x^3 + x + 1)y = x^4 - 5x^3 + x^2 + x\) $\mathrm{USp}(4)$ 3
60916.a.243664.1 60916.a \(y^2 + x^3y = 2x^3 - x^2 - 2x + 1\) $\mathrm{USp}(4)$ 3
61099.a.61099.1 61099.a \(y^2 + (x^3 + 1)y = -3x^4 + 3x^3 + 2x^2 - 2x\) $\mathrm{USp}(4)$ 3
61127.a.61127.1 61127.a \(y^2 + (x^3 + x + 1)y = 2x^5 + 3x^4 - x^2\) $\mathrm{USp}(4)$ 3
61553.a.61553.1 61553.a \(y^2 + (x^3 + x + 1)y = -x^4 - 3x^3 + x^2 + x\) $\mathrm{USp}(4)$ 3
62233.a.62233.1 62233.a \(y^2 + (x^3 + x + 1)y = -3x^4 + x^3 + 5x^2 - 5x\) $\mathrm{USp}(4)$ 3
62411.b.62411.1 62411.b \(y^2 + y = x^5 - x\) $\mathrm{USp}(4)$ 3
62563.a.62563.1 62563.a \(y^2 + (x^3 + x + 1)y = -3x^4 + x^3 + 3x^2 - x\) $\mathrm{USp}(4)$ 3
62924.a.251696.1 62924.a \(y^2 + x^3y = -x^4 - 2x^3 + 6x^2 - 4x + 1\) $\mathrm{USp}(4)$ 3
63506.a.127012.1 63506.a \(y^2 + (x^3 + 1)y = 2x^3 + 2x^2 - x\) $\mathrm{USp}(4)$ 3
63707.a.445949.1 63707.a \(y^2 + (x^3 + x + 1)y = x^5 + x^3 + 6x^2 + 2x\) $\mathrm{USp}(4)$ 3
64237.a.64237.1 64237.a \(y^2 + (x^3 + x^2 + 1)y = x^3 - 3x\) $\mathrm{USp}(4)$ 3
64829.a.64829.1 64829.a \(y^2 + (x^3 + x + 1)y = x^4 + x^3 + x^2 + x\) $\mathrm{USp}(4)$ 3
65167.b.65167.1 65167.b \(y^2 + (x^3 + x + 1)y = x^5 - x^4 - 5x^3 - 2x^2 + x\) $\mathrm{USp}(4)$ 3
65814.a.394884.1 65814.a \(y^2 + (x^3 + 1)y = x^5 + x^4 - x^2 - 3x + 2\) $\mathrm{USp}(4)$ 3
65869.a.65869.1 65869.a \(y^2 + y = x^6 - x^5 - x^3 + x\) $\mathrm{USp}(4)$ 3
66161.a.66161.1 66161.a \(y^2 + y = x^6 - x^5 - x^4 - x^3 + x^2 + x\) $\mathrm{USp}(4)$ 3
66601.a.66601.1 66601.a \(y^2 + (x^3 + 1)y = -x^4 + 5x^3 + 16x^2 + 11x + 2\) $\mathrm{USp}(4)$ 3
67006.a.134012.1 67006.a \(y^2 + (x^3 + 1)y = 3x^4 + x^3 - x^2\) $\mathrm{USp}(4)$ 3
67203.c.604827.1 67203.c \(y^2 + (x^3 + x + 1)y = -x^4 - x^2 + 2\) $\mathrm{USp}(4)$ 3
68209.a.68209.1 68209.a \(y^2 + (x^3 + 1)y = x^5 - 3x^4 + 3x^3 - x\) $\mathrm{USp}(4)$ 3
70351.a.70351.1 70351.a \(y^2 + (x^3 + x^2 + x)y = -x^4 + x^3 + 3x^2 - 4x + 1\) $\mathrm{USp}(4)$ 3
70450.c.704500.1 70450.c \(y^2 + (x^3 + 1)y = -2x^4 + x^3 + 4x^2 - 3x\) $\mathrm{USp}(4)$ 3
70469.a.70469.1 70469.a \(y^2 + (x^3 + x^2 + 1)y = 2x^4 + x^3 + 4x^2 + x + 2\) $\mathrm{USp}(4)$ 3
71407.a.71407.1 71407.a \(y^2 + x^3y = -2x^4 - 3x^3 + x^2 + 3x + 1\) $G_{3,3}$ 3
Next

Download all search results for